2009
DOI: 10.1577/t08-051.1
|View full text |Cite
|
Sign up to set email alerts
|

Water Velocity, Turbulence, and Migration Rate of Subyearling Fall Chinook Salmon in the Free‐Flowing and Impounded Snake River

Abstract: We studied the migratory behavior of subyearling fall Chinook salmon Oncorhynchus tshawytscha in free-flowing and impounded reaches of the Snake River to evaluate the hypothesis that velocity and turbulence are the primary causal mechanisms of downstream migration. The hypothesis states that impoundment reduces velocity and turbulence and alters the migratory behavior of juvenile Chinook salmon as a result of their reduced perception of these cues. At a constant flow (m 3 /s), both velocity (km/d) and turbulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(88 citation statements)
references
References 31 publications
2
82
4
Order By: Relevance
“…The long distances between release locations and the dam (89-225 km) and the slowing of migration rates (Tiffan et al, 2009) would increase exposure of fish to predators and increase total predation mortality. The results from this study demonstrated that smallmouth bass predation accounted for a large portion (15%-37%) of age-0 Chinook salmon mortality from release to passage at Lower Granite Dam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long distances between release locations and the dam (89-225 km) and the slowing of migration rates (Tiffan et al, 2009) would increase exposure of fish to predators and increase total predation mortality. The results from this study demonstrated that smallmouth bass predation accounted for a large portion (15%-37%) of age-0 Chinook salmon mortality from release to passage at Lower Granite Dam.…”
Section: Discussionmentioning
confidence: 99%
“…Survival (95% CIs) of hatchery-release groups from release to Lower Granite Dam as estimated by Arnsberg et al (2017aArnsberg et al ( , 2017b Reservoir (Miller et al, 2002;Tiffan, Kock, Haskell, Connor & Steinhorst, 2009). Sampling was limited to this stretch of river because of safety issues and time constraint.…”
Section: Study Areamentioning
confidence: 99%
“…Water temperature, velocity, and turbidity change during flooding and have been correlated with dispersal rates of riverine fishes (Fernandes 1997;Nunn et al 2010;Rakowitz et al 2008;Swanberg 1997;Sykes et al 2009;Tiffan et al 2009). Less obvious are changes in channel water chemistry associated with large-scale flooding and catchment runoff, such as increases in the concentration of dissolved organic nitrogen (DON; Lewis 2002;Martin and Harrison 2011).…”
Section: H1: Large-scale Versus Localized Floodingmentioning
confidence: 99%
“…Tiffan et al. () showed that subyearlings delay downstream movement in these transitional habitats of Lower Granite Reservoir, which may increase the duration of their exposure to predators. Naughton et al.…”
mentioning
confidence: 99%